2009
DOI: 10.1136/hrt.2008.160309
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative patient effective dose and acute radiation-induced chromosomal DNA damage in children with congenital heart disease

Abstract: BackgroundThe seventh Committee on "Biological Effects of Ionizing Radiation" (BEIR VII, 2006) underlines "the need of studies of infants who are exposed to diagnostic radiation because catheters have been placed in their hearts". Objective To determine the lifetime attributable risk (LAR) of cancer associated with the estimated cumulative radiological dose in 59 children (42 male, age 2.863.2 years) with complex congenital heart disease, and to assess chromosomal DNA damage after cardiac catheterisation proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
152
0
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 200 publications
(160 citation statements)
references
References 46 publications
(39 reference statements)
3
152
0
3
Order By: Relevance
“…22 Children are at least four times more sensitive than adults to the induction of cancer, as they have more rapidly dividing cells than adults and have longer life expectancy. [23][24][25] Unfortunately, pediatricians are often unaware of these risks. 26 The long-term risk associated with radiation exposure should be considered in the risk-benefit assessment behind appropriate prescription of diagnostic testing.…”
Section: Discussionmentioning
confidence: 99%
“…22 Children are at least four times more sensitive than adults to the induction of cancer, as they have more rapidly dividing cells than adults and have longer life expectancy. [23][24][25] Unfortunately, pediatricians are often unaware of these risks. 26 The long-term risk associated with radiation exposure should be considered in the risk-benefit assessment behind appropriate prescription of diagnostic testing.…”
Section: Discussionmentioning
confidence: 99%
“…Selon Ait-Ali (Ait-Ali et al, 2010) les procédures les plus irradiantes sont les procédures de cardiologie interventionnelle à visée diagnostique et/ou thérapeu-tique et les scanners. La dose de radiation délivrée lors d'un examen scanner est en moyenne 10 à 100 fois plus élevée que celle délivrée lors d'un examen radiologique conventionnel.…”
Section: Contexteunclassified
“…Data from Italy raised a concern that children with congenital heart disease are exposed to a significant cumulative dose of radiation. 56 Indirect cancer risk estimations and direct DNA studies showed that children with congenital heart disease are exposed to a significant radiation dose and emphasised the need for strict radiation dose optimisation in children. The accompanying editorial from Hoffmann and Bremerich expanded on the risks.…”
Section: Catheter Interventionmentioning
confidence: 99%